Post-translational modifications in health and disease - Vidal, Cecilio J. (Springer, 2011)
Post-translational modifications serve many different purposes in a wide variety of cellular processes,such as protein synthesis, folding, stability, the housing of prosthetic groups, vesicular trafficking,protein targeting to particular cell stores, exocytosis and endocytosis, the biogenesis of cell organelles and basal lamina. Signal transduction, with functional effects for enzyme regulation and metabolic control on the one hand, and gene expression, cell division, differentiation and apoptosis on the other, is also prominent. Post-translational Modifications in Health and Disease provides the reader with nineteen reviews that stimulate further investigations in the proteomic field - focusing on functional and pathological aspects of protein prenylation, the incorporation of glycosylphosphatidylinositol (GPI) moieties, oxidation, nitrosylation, glycosylation, and phosphorylation and dephosphorylation - with emphasis on their outcome for protein-protein interaction phenomena and down-stream effects. Additional chapters are devoted to protein ubiquitination, sumoylation and endoplasmic reticulum-associated degradation (ERAD), the influence of histone modification on gene expression and DNA repair, and proteolytic processing of intracellular and basal lamina proteins. This book will be of particular significance to researchers, clinicians, and students of biology, pharmacy and medicine.